Overlapping SigH and SigE sigma factor regulons in Corynebacterium glutamicum - Busche, Tobias; Dostálová, Hana; Rucká, Lenka; Holátko, Jiří; Barvík, Ivan; Štěpánek, Václav; Pátek, Miroslav; Kalinowski, Jörn (Frontiers in Microbiology, 2023)
The sigma H (σH) and sigma E (σE) subunits of Corynebacterium glutamicum RNA polymerase belong to Group 4 of sigma factors, also called extracytoplasmic function (ECF) sigma factors. Genes of the C. glutamicum (σH)regulon that are involved in heat and oxidative stress response have already been defined, whereas the genes of the σE regulon, which is involved in cell surface stress response, have not been explored until now. Using the C. glutamicum RES167 strain and its derivative C. glutamicum delta-cseA with a deletion in the anti-σE gene, differential gene expression was analyzed by RNA sequencing. We found 296 upregulated and 398 downregulated genes in C. glutamicum delta-cseA compared to C. glutamicum RES167. To confirm the functional link between σE and the corresponding promoters, we tested selected promoters using the in vivo two-plasmid system with gfpuv as a reporter gene and by in vitro transcription. Analyses with RNAP+σH and RNAP+σE, which were previously shown to recognize similar promoters, proved that the σH and σE regulons significantly overlap. The σE-controlled genes were found to be involved for example in protein quality control (dnaK, dnaJ2, clpB, and clpC), the regulation of Clp proteases (clgR) and membrane integrity maintenance. The single-promoter analyses with σH and σE revealed that there are two groups of promoters: those which are exclusively σH-specific, and the other group of promoters, which are σH/σE-dependent. No exclusively σE-dependent promoter was detected. We defined the consensus sequences of exclusively σH-regulated promotors to be –35 GGAAt and –10 GTT and σH/σE-regulated promoters to be –35 GGAAC and –10 cGTT. 15 genes were found to belong to the σH/σE regulon. Homology modeling showed that there is a specific interaction between Met170 in σH and the nucleotides –31 and –30 within the non-coding strand (AT or CT) of the σH-dependent promoters. In σE, Arg185 was found to interact with the nucleotides GA at the same positions in the σE-dependent promoters.